Neoliberalism and the (Im)possibility of the Affective Novel. Issue 8 (3rd August 2022) - Goldfarb, Jason
ABSTRACT: This paper begins by mapping what it calls the 'affect-neoliberal' debate in contemporary literary studies. This debate, centred on the relationship between the personal-affective novel and neoliberalism, contains two dominant positions, termed capitulationist and subversion views. The former asserts that the personal novel form, as tied to the particular, fails to represent late capitalism; the latter argues that affective literature is always-already social, potentially offering a poignant critique of neoliberal individualism. Yet instead of favouring one position over the other, this paper claims that each view is ultimately one-sided: capitulationists fail to see how the social mediates the personal, thus missing the possibility of self-critical affective novels; the subversion view fails to see how the social is caught up in the personal and neoliberal, thus missing the capitulatory aspect of so-called 'impersonal' affect. Ultimately, this paper argues that the task is not to think the affective novel in its purely personal (capitulatory) or social (subversive) dimension, but to see it as antagonistically situated between the two. This perspective entails thinking the impossibility of the affective novel, or the way such novels may think the personal-affective as disruptively mediated by neoliberalism, a position derived from Kazuo Ishiguro's Never Let Me Go.